2006
DOI: 10.1242/dev.02598
|View full text |Cite
|
Sign up to set email alerts
|

Ptf1a determines horizontal and amacrine cell fates during mouse retinal development

Abstract: The vertebrate neural retina comprises six classes of neurons and one class of glial cells, all derived from a population of multipotent progenitors. There is little information on the molecular mechanisms governing the specification of cell type identity from multipotent progenitors in the developing retina. We report that Ptf1a, a basic-helix-loop-helix (bHLH) transcription factor, is transiently expressed by post-mitotic precursors in the developing mouse retina. Recombination-based lineage tracing analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
262
4
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(285 citation statements)
references
References 44 publications
(74 reference statements)
18
262
4
1
Order By: Relevance
“…A similar finding has been reported in the retina (15). Altogether, it is likely that the Ptf1a gene may control the expression of key regulatory genes in certain GABAergic phenotypes (such as PCs and interneurons in the cerebellum and spinal cord), although we can only speculate as to which genes are targeted by Ptf1a.…”
Section: Ptf1a Is Required For the Generation And Survival Of Pcs Andsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar finding has been reported in the retina (15). Altogether, it is likely that the Ptf1a gene may control the expression of key regulatory genes in certain GABAergic phenotypes (such as PCs and interneurons in the cerebellum and spinal cord), although we can only speculate as to which genes are targeted by Ptf1a.…”
Section: Ptf1a Is Required For the Generation And Survival Of Pcs Andsupporting
confidence: 87%
“…Ptf1a is also required for the generation of dorsal horn GABAergic interneurons in the spinal cord, and, in its absence, Ptf1a-derived cells adopt a glutamatergic phenotype (14). A recent study in the retina shows that inactivation of Ptf1a leads to a fate switch in horizontal and amacrine cell precursors that causes them to adopt a ganglion cell fate (15). We have examined the role of Ptf1a in the development of the cerebellum by analyzing the phenotype of mice lacking the complete Ptf1a coding sequence (Ptf1a Cre knockin).…”
mentioning
confidence: 99%
“…6G-L) (Qiu et al, 2008), consistent with the abnormal differentiation of most amacrine cells in this layer of the mutant retina. It has been shown that Neurod1, Math3 and Ptf1a are required for specifying amacrine cells and Bhlhb5 and Nr4a2 for differentiation of GABAergic amacrine cells (Feng et al, 2006;Fujitani et al, 2006;Inoue et al, 2002;Jiang and Xiang, 2009;Nakhai et al, 2007). Similarly, there was a significant increase in expression of Prox1, Ptf1a, Lim1 and Ngn2, all transcription factor genes involved in horizontal cell development (Akagi et al, 2004;Dyer et al, 2003;Fujitani et al, 2006;Liu et al, 2000b;Nakhai et al, 2007;Poche et al, 2007), within the INBL of Pou4f2 null retinas (Fig.…”
Section: Safeguard Mechanism By Transcription Factors To Ensure Rgc Fmentioning
confidence: 97%
“…Nevertheless, deletion of both Oc1 and Oc2 together leads to complete failure of HC genesis, confirming the redundancy of these two factors in the HC lineage. Two major regulators involved in the HC fate are FoxN4 and Ptf1a, with FoxN4 being upstream (29,30). We recently showed that Oc1 functions together with Ptf1a at the same level in the regulatory hierarchy to promote the HC fate and inhibit the amacrine cell fate (14).…”
Section: Potential Mechanisms By Which Oc1 and Oc2 Function In Multiplementioning
confidence: 99%